Cytotoxicity and migration of fibroblasts on two types of calcium sulfate dihydrate. Issue 1 (27th July 2015) - Teparat‐Burana, Thitiwan; Onsiri, Natnicha; Jantarat, Jeeraphat
Abstract: Aim: The aim of the present study was to compare cytotoxicity and migration ability of L929 on medical‐grade calcium sulfate dihydrate (MCS) with commercial calcium sulfate dihydrate (CCS). Methods: Samples of both freshly‐mixed and set states of MCS and CCS were extracted in culture medium and tested for cytotoxicity according to International Organization of Standardization 10993‐5:2009. The 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay was used, and the percentage of cell viability was calculated. Thirty petri dishes were divided into three equal groups: polystyrene (control), CCS, and MCS. In each petri dish, triplicate wells were made on the agarose overlay on the material. The central well was occupied with L929 cell suspension, one well was filled with platelet‐derived growth factor‐BB, and the remaining well with Hanks' Balanced Salt Solution. After incubation, the migration distances were measured and the corrected migration distances were calculated. The final step involved scanning electron microscopy (SEM). Results: The CCS had significantly less cell viability than MCS at a high extracted concentration ( P < 0.001) in both samples. The mean corrected migration of MCS was significantly greater than that of CCS ( P < 0.05). SEM showed that L929 cells on MCS exhibited an elongated spindle shape. Conclusion: MCS was less cytotoxic and provided greater migration of L929 fibroblasts compared with CCS.